2023
DOI: 10.1002/cbic.202200687
|View full text |Cite
|
Sign up to set email alerts
|

Stairway to Stereoisomers: Engineering Short‐ and Medium‐Chain Ketoreductases To Produce Chiral Alcohols

Abstract: The short-and medium-chain dehydrogenase/reductase superfamilies are responsible for most chiral alcohol production in laboratories and industries. In nature, they participate in diverse roles such as detoxification, housekeeping, secondary metabolite production, and catalysis of several chemicals with commercial and environmental significance. As a result, they are used in industries to create biopolymers, active pharmaceutical intermediates (APIs), and are also used as components of modular enzymes like poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 233 publications
(271 reference statements)
0
10
0
Order By: Relevance
“…16 Shanbhag thoroughly described the engineering of short- and medium-chain dehydrogenases/reductases and their application in the production of chiral synthons. 17 Recently, Qiao et al reviewed protein engineering and the immobilization of keto reductases in the synthesis of chiral alcohols. 105 Here we shine a spotlight on the past five years of the engineering of microbial dehydrogenases towards the synthesis of chiral precursors of drugs and bioactive molecules with industrial applications.…”
Section: Protein Engineering Of Carbonyl Reductasesmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Shanbhag thoroughly described the engineering of short- and medium-chain dehydrogenases/reductases and their application in the production of chiral synthons. 17 Recently, Qiao et al reviewed protein engineering and the immobilization of keto reductases in the synthesis of chiral alcohols. 105 Here we shine a spotlight on the past five years of the engineering of microbial dehydrogenases towards the synthesis of chiral precursors of drugs and bioactive molecules with industrial applications.…”
Section: Protein Engineering Of Carbonyl Reductasesmentioning
confidence: 99%
“…Some recent reviews have updated the application of ketoreductases in asymmetric synthesis. [15][16][17]35,105 Li et al described the use of ketoreductases including engineered enzymes that were reported between 2018 and 2020, in the asymmetric synthesis of pharmaceuticals. 15 Another recent review elaborated on the use of wild type and engineered anti-Prelog ADHs in the synthesis of optically active alcohols.…”
Section: Protein Engineering Of Carbonyl Reductasesmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, another important distinction between ADHs is the preference for the coenzyme that can be NADH or NADPH. In general, most of the known natural ADHs are classified as Prelog and comprise both NAD‐ and NADP‐dependent enzymes [8c–e] . In contrast, anti‐Prelog ADHs are far less ubiquitous in nature and almost all of them are NADP(H) dependent [8d,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are widely applied in the pharmaceutical industry as key chemical catalysts. [3,4] So far, only two SDR superfamily members have been confirmed to be involved in the molecular machineries for the analogous biosynthesis of fatty acids (FAS), polyketides (PKS) and non-ribosomal peptides (NRPS): the 3-ketoacyl reductase (KR) and enoyl reductase (ER). They are indispensable and conserved core enzymatic scaffolds in these metabolic routes for controlling energy supply, transcription and signaling.…”
Section: Introductionmentioning
confidence: 99%